STUDI ORGANOLEPTIK TEMPE DARI PERBANDINGAN KACANG KOMAK (Lablab purpureus (L.) Sweet) DENGAN BERBAGAI KONSENTRASI RAGI DAN LAMA FERMENTASI SEBAGAI BAHAN PENYUSUNAN BROSUR - Haeratul Fazrin; Iwan Doddy Dharmawibawa; Sucika Armiani (Bioscientist : Jurnal Ilmiah Biologi, 2020)
Tempeh is popular with Indonesian people, besides its price is relatively cheap and tastes good, tempeh also has high vegetable protein content. The objectives of this study are: 1) to find out the organoleptic comparison of the Hyacinth Bean (Lablab purpureus (L.) Sweet) tempeh at various concentrations of yeast; 2) knowing the organoleptic comparison of tempeh Hyacinth Bean (Lablab purpureus (L.) Sweet) on various fermentation periods; and 3) implementing research results as material for preparing brochures for the community. This type of research is pure experimental research. Using Random Group Design (RBD). The yeast concentration consisted of 1.5%, 2%, and 2.5% treatments, while the fermentation time was 24 hours, 30 hours and 36 hours. Organoleptic parameters include color, taste, texture, and aroma. Data collection techniques used in this study were carried out by observation, questionnaires, organoleptic test observations, and brochure validation sheets. Data analysis techniques used Analysis of Variance (ANOVA) with a significance level of 5%. The results showed that, variations in yeast concentration and length of fermentation in making tempeh Hyacinth Bean (Lablab purpureus (L.) Sweet) significantly influenced the aroma, taste, and texture, while the concentration of yeast and duration of fermentation did not significantly influence the tempe color of Hyacinth Bean (Lablab purpureus (L.) Sweet). The results of the brochure assessment qualification analysis show that, the brochure is suitable for use by the public.